2016
DOI: 10.1080/14760584.2017.1247700
|View full text |Cite
|
Sign up to set email alerts
|

Varicella prevention in Costa Rica: impact of a one-dose schedule universal vaccination

Abstract: To describe the impact following a 1-dose Varicella vaccination schedule introduced in Costa Rica in September 2007. Areas covered: This is a retrospective review using epidemiologic surveillance national databases of varicella cases and hospitalizations, period 2000-2015. We analyzed age-related varicella incidence cases and hospitalization trends before and after the vaccine introduction. Expert commentary: Varicella vaccine coverage among children 16 months age increased from 76% in 2008 to 95% in 2015. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 13 publications
1
22
0
4
Order By: Relevance
“…All studies have shown impressive reductions in disease incidence compared with the pre-vaccination era. After one-dose programs, reductions up to 74% have been recorded [56]. Whereas reductions exceeding 90% have been recorded after two-dose schedules [37,57,58].…”
Section: Evidence For Varicella Vaccinationmentioning
confidence: 99%
“…All studies have shown impressive reductions in disease incidence compared with the pre-vaccination era. After one-dose programs, reductions up to 74% have been recorded [56]. Whereas reductions exceeding 90% have been recorded after two-dose schedules [37,57,58].…”
Section: Evidence For Varicella Vaccinationmentioning
confidence: 99%
“…Increasing the varicella vaccination coverage rate significantly decreased the incidence of the disease and hospitalizations due to complications. Both direct and indirect effects of universal varicella vaccination have been reported elsewhere . The effectiveness of the single‐ and double‐dose varicella vaccines was 80% (range, 20–100%) and 93% (range, 84–98%), respectively .…”
Section: Discussionmentioning
confidence: 57%
“…Both direct and indirect effects of universal varicella vaccination have been reported elsewhere. [17][18][19][20][21][22][23][24][25] The effectiveness of the single-and double-dose varicella vaccines was 80% (range, 20-100%) and 93% (range, 84-98%), respectively. 26 The single-dose varicella vaccination program was able to prevent mortality while a double-dose was able to prevent morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The vaccination strategy used in our region has significantly reduced the burden of disease, as seen in other countries. [13][14][15][16][17][18] However, there was a slight increase in the incidence of all ages after the exclusion of the dose at 15 months from the public funded vaccination schedule. This modification was made in the context of laws to reduce health expenditure and seeking cohesion with the vaccine schedules of other Autonomous Communities.…”
Section: Discussionmentioning
confidence: 99%